Cannabis consumption among elite athletes in Germany - Udelhoven, T.; Brixius, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Cannabis is increasingly consumed by elite athletes, leading to a surge in doping sanctions in Germany. The prelude to the 2024 Olympic Games introduces specific challenges and regulatory changes related to cannabis. This study investigates cannabis consumption among elite athletes in Germany to identify opportunities for more targeted education among at-risk target groups and to enhance protection against inadvertent doping violations within the context of anti-doping efforts. METHODS: Through an online survey with elite athletes, this research provides insights into cannabis consumption behaviour and competence regarding the topic of cannabis among elite athletes. 380 out of 512 participants completed the online survey and were included in the analysis; 259 (68.2%) of them were male, and 121 (31.8%) were female. Among the participants, 175 (46.1%) were u19 years old, 61 (16.1%) u23 years old, and 144 (37.9%) o23 years old. RESULTS: Depending on factors such as age group, gender, migration background, and/or sport, athletes are at an elevated risk of unintentional rule violations and subsequent doping sanctions related to cannabis. Over a quarter (28.1%) of German elite athletes report lifetime cannabis consumption. In group comparisons, the prevalence of cannabis consumption is significantly higher among athletes over 23 years (o23: 51,4%; u23: 28,3%; u19: 8,3%), male athletes (m: 31,6%; f: 20.8%), and athletes from the sports of basketball (76,2%), and American football (68,2%). The frequency of cannabis consumption is lower than lifetime use, with 9.6% of elite athletes using THC occasionally to regularly, and 5,7% for CBD consumption. Higher rates of THC consumption are observed among athletes from the sports American football (36,4%), basketball (28,6%), and baseball/softball (26,7%), athletes over 23 years old (o23: 16,6%; u23: 13,3%; u19: 2,4%), male athletes (m: 11,8%; f: 5,0%), and team athletes (t: 13,4%; i: 5,2%). CBD consumption rates are generally lower, with the highest prevalence observed in athletes from American football at 22,7%. Cannabis consumption is primarily motivated by pleasure (52,2%). The survey indicates a notable 85,8% knowledge deficit on cannabis among athletes, with a marked disparity in prevalence between those with and without migration background (wm: 93,7%; nm: 82,5%). CONCLUSION: The growing prevalence of cannabis use among athletes, coupled with its extended detectability and existing knowledge gaps, may collectively contribute to the emerging doping issue in elite sports. Implementing targeted education for the risk groups, including (1) athletes over 23 years old, (2) male athletes, and athletes from the sports of (3) basketball, (4) American football, (5) rowing, and (6) baseball/ softball, is recommended to mitigate future doping violations related to cannabis consumption.